Battery charger using solar panel energy - Tan, Zhenyu. (2011)
Solar power is the conversion of sunlight into electrical power, and it is currently the most available source of energy. Conversion of energy can be easily done using Photovoltaic’s. Also referred to as solar electric, Photovoltaic’s offers the ability to generate electricity in a clean, quiet and renewable way. It makes use of the abundant energy from the sun, to generate electricity without the production of harmful carbon dioxide (CO2) emissions.